EFFECTS OF ROTATION ON THE MINIMUM MASS OF PRIMORDIAL PROGENITORS OF PAIR-INSTABILITY SUPERNOVAE - Chatzopoulos, E.; Craig Wheeler, J. (The Astrophysical journal, 2012)
The issue of which stars may reach the conditions of electron/positron pair-formation instability is of importance to understand the final evolution both of the first stars and of contemporary stars. The criterion to enter the pair-instability regime in density and temperature is basically controlled by the mass of the oxygen core. The main-sequence masses that produce a given oxygen core mass are, in turn, dependent on metallicity, mass loss, and convective and rotationally induced mixing. We examine the evolution of massive stars to determine the minimum main-sequence mass that can encounter pair-instability effects, either a pulsational pair-instability supernova (PPISN) or a full-fledged pair-instability supernova (PISN). We concentrate on zero-metallicity stars with no mass-loss subject to the Schwarzschild criterion for convective instability, but also explore solar metallicity and mass loss and the Ledoux criterion. As expected, for sufficiently strong rotationally induced mixing, the minimum main-sequence mass is encountered for conditions that induce effectively homogeneous evolution such that the original mass is converted almost entirely to helium and then to oxygen. For this case, we find that the minimum main-sequence mass is about 40 M sub([middot in circle]) to encounter PPISN and about 65 M sub([middot in circle]) to encounter a PISN. The implications of these results for the first stars and for contemporary supernovae are discussed.